Leveraging Information Technology for Rapid Product Development in Sports Equipment: A Sport Psychology Perspective - Jaquelyn Litchfield; Emma Frederick (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Athletes constantly push the limits of their talents in the competitive world of sports, where greatness is the goal. Sports equipment, which has developed from simple tools into complex extensions of the athlete, is at the center of this quest. Information technology is now driving innovation in sports equipment, with developments like computer-aided design and data analytics. Sports gear affects the athlete's mental state and is more than a physical accessory. This research investigates the integration of sport psychology and information technology in the design of sporting goods. It demonstrates how these seemingly unrelated fields work together to produce a comprehensive strategy that improves equipment performance and supports players' psychological well-being. The intersection of sport psychology and information technology is the basis of our investigation. Due to this synergy, technology can now collect and analyze information on athletic performance and psychological states. As a result, athletes and their gear have a close relationship since the equipment is tailored to each athlete's unique characteristics. By satisfying both physical and psychological requirements, this integration enables athletes to perform at previously unheard-of heights.